PENGARUH MOTIVASI TERHADAP KINERJA GURU DIMODERASI KEPEMIMPINANTRANSFORMASIONALDANBUDAYAORGANISASIONAL (Studi pada smp Negeri di Kecamatan Ulujami Kabupaten Pemalang) (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to examine and analyze the effect of motivation on the performance moderated transformational leadership and organizational budata teacher at Junior High School in the district of Pemalang Ulujami. The population in this study is a civil servant teachers Junior High School in the district of Pemalang Ulujami many as 125 teachers, primary data were collected using a questionnaire instruments to measure variables using a Likert scale. Hypothesis test used in this study is t-test at a significant level (a) 0.05. The results showed that motivation positive and significant impact on teacher performance, transformational leadership influence on the performance of the teacher, organizational culture does not affect the performance of teachers, transformational leadership moderating influence on the performance of teachers' motivation, organizational culture moderates the effect of motivation on teacher performance. Keywords: motivation, transformational leadership, organizational culture, the performance of teachers.